2008
DOI: 10.1007/s11130-008-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Lime-Cooking and Tortilla Making Properties of Quality Protein Maize Hybrids Grown in Mexico

Abstract: Eleven experimental and three commercial white quality protein maize (QPM) hybrids and two regular endosperm controls were planted at Celaya, Guanajuato, Mexico with the aim of comparing grain physical characteristics, protein quality, lime-cooking and tortilla making properties. All genotypes were planted under irrigation using a density of 80,000 plants/ha and fertilized with 250 kg N-60 P-60 K per hectare. When compared with the controls these QPM genotypes had lower test (77.4 vs. 76.5 kg/hL) and 1,000 ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
2
6
0
7
Order By: Relevance
“…This compared favorably with results of SernaSaldivar et al [16] who reported DML in the range of 5.0-7.3%, which is within values commonly seen for the genotypes preferred by the industry. Yellow hybrid maize (hard, 40 min) produced the nixtamal with the highest moisture content, but its tortillas had the lowest moisture (Table 3).…”
Section: Quality Of Nixtamal and Tortillassupporting
confidence: 86%
See 1 more Smart Citation
“…This compared favorably with results of SernaSaldivar et al [16] who reported DML in the range of 5.0-7.3%, which is within values commonly seen for the genotypes preferred by the industry. Yellow hybrid maize (hard, 40 min) produced the nixtamal with the highest moisture content, but its tortillas had the lowest moisture (Table 3).…”
Section: Quality Of Nixtamal and Tortillassupporting
confidence: 86%
“…Statistical analysis showed differences between landraces and hybrid maize in all physical variables evaluated ( [15] reported for different accessions of maize, whereas the TW of the hybrids was higher than those reported for hybrids by other authors [16,17]. TW has been associated with grain hardness [18].…”
Section: Physical Grain Propertiesmentioning
confidence: 69%
“…Mexico with a population of 105 million people in year 2005 is one of the countries with the highest per capita consumption of maize [1]. Among the largest diversity of genetic resources of Mexican maize, pigmented genotypes as purple, red, and blue are the most common [2].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, tortillas are prepared with white maize [2], though in recent years, blue maize has also been used for their preparation. This is because blue grain maize contains anthocyanins, which are considered natural antioxidants that can scavenge free radicals that damage bio-molecules.…”
Section: Introductionmentioning
confidence: 99%